2004
DOI: 10.1038/labinvest.3700112
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer invasion is influenced more by expression of a CD44 isoform including variant 9 than by Muc18

Abstract: The standard form of cell adhesion glycoprotein CD44 is a metastasis suppressor in prostate cancer. However, we previously showed by RT-PCR and Western blotting that cancer overexpresses unique CD44 variant v7-v10 isoforms. Muc18 is another cell adhesion marker reportedly overexpressed by prostate cancer. Matched frozen section-confirmed tumor and benign tissues were harvested from 10 prostatectomy specimens and tumor was microdissected from two lymph node metastases. Tissues were homogenized for RNA preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 41 publications
1
57
0
Order By: Relevance
“…This possibility certainly exists considering that CD44 has previously been implicated in facilitating PCa cell invasion in vitro (e.g. Lokeshwar et al, 1995;Draffin et al, 2004;Omara-Opyene et al, 2004). In this regard, it is of interest to note that the LAPC-9 tumors, which were initially isolated from a bony metastasis, contain many more CD44 þ cells than LAPC-4 tumors, which were originally isolated from a lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This possibility certainly exists considering that CD44 has previously been implicated in facilitating PCa cell invasion in vitro (e.g. Lokeshwar et al, 1995;Draffin et al, 2004;Omara-Opyene et al, 2004). In this regard, it is of interest to note that the LAPC-9 tumors, which were initially isolated from a bony metastasis, contain many more CD44 þ cells than LAPC-4 tumors, which were originally isolated from a lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although CD44 expression is reported to be reduced in metastases (Nagabhushan et al, 1996;De Marzo et al, 1998;Noordzij et al, 1999), the CD44 þ PCa cells are found to predominate in two visceral metastases (Liu et al, 1999). Similar to expression studies, the potential role of CD44 in PCa development and metastases is controversial -although some studies show a tumor-suppressive function of CD44 in overexpression experiments (Gao et al, 1997(Gao et al, , 1998, many other studies implicate CD44 in PCa cell proliferation, adhesion, migration, and invasion in vitro as well as in metastatic dissemination in vivo (Lokeshwar et al, 1995;Paradis et al, 1998;Liu et al, 1999;Draffin et al, 2004;Omara-Opyene et al, 2004). Many studies mentioned above utilize either human tissues to carry out correlative immunohistochemistry (IHC) or bulk-cultured PCa cells to carry out overexpression experiments and the key experiment of using purified CD44 þ and CD44 À cells from the same culture or tumor to compare their potentially different biological and tumorigenic properties has not yet been done.…”
Section: Introductionmentioning
confidence: 89%
“…The role of CD44s and CD44v in CaP development and progression is different, with studies showing both tumorinhibiting (CD44s) and tumor-promoting (CD44v) effects [13][14][15]. To date, no studies have investigated the correlation between CD44 expression and radiosensitivity of CaP.…”
mentioning
confidence: 98%
“…Many cancer-associated genes such as CD44 are alternatively spliced [9] . Certain CD44 variants have been reported to have functional significance in prostate cancer [10] . Amongst these, the standard isoform CD44s has been extensively studied and its downregulation has been linked to high Gleason scores [5,11,12] .…”
Section: Discussionmentioning
confidence: 99%